Enhancement of the English for specific purposes methodology applied at an Aviation Military School in Salinas. - Almeida Pacheco, Víctor Alfonso (2018)
The purpose of this research is to analyze the Methodology of an “English for Specific Purposes” (ESP) Aviation course used for flight operations and Radiotelephony operations at Escuela Superior Militar de Aviación “Cosme Renella Barbatto” (ESMA) in Salinas, Ecuador. The analysis of this research was both quantitative and qualitative; hence, the design for this research is a mixed method approach. The instruments used to obtain the collected data were a mock Aviation English test, an interview for teachers, and a survey for the students. For this study, fifteen pilot cadets of first year were considered as well as the aviation English module instructor. Teachers and students’ perceptions towards the Aviation English module were monitored, observed and analyzed. The results of this research showed that some aspects regarding the Methodology of the Aviation English module taught at ESMA must be improved since not all the cadets were familiarized with ICAO’s Language Proficiency Requirements manual or The ICAO Standardized Phraseology manual. This investigation proposes a Blended Learning design as a contribution to improve the methodology of aviation English course ta ESMA.